O trabalho na velhice: novas possibilidades - Oliveira, José Bernardo Enéias de (2006)
The present research shows up capability and possibilities for elderly people (senior citizens) to (re) socialize by work and new occupations, even considering the natural aspects of the aging process. It recognizes the development of their skills in the learning process, for a continuous social reproduction, as a way of social insertion and quality of life. This study discusses the adaptation of elderly people to the new social model when cultural values and subjective perception create barriers in socialization thus unbalancing emotional aspects and making functional and social changes. These non-perceptive variables damage the social adaptation specifically concerning the decision-making capability and performance of actions with their own means: autonomous and functional independence. The investigations are based on social-economic transformations through which the world is going, mainly in issues of the population s aging process and the social reproduction as a way to survive, making new prospects possible for elderly people, thus not regarding them as a non-productive part of the population